Acessibilidade digital em ONGs brasileiras para pessoas com deficiência: análises, perspectivas e desafios para a inclusão tecnológica e social - Justo, Carmen Silvia Porto Brunialti (2023)
Digital information and communication technologies have enabled the expansion of informational and communication resources across various organizations and companies, catering to diverse audiences. Among these resources, digital accessibility for people with disabilities through assistive technology software and devices on various platforms facilities access to websites and platforms. Digital accessibility standards are proposed by W3C Consortium and the recommendations outlined in the Brazilian Inclusion Law (LBI/2015). This law, encompassing chapters 63 to 73, mandates effective access to information and communication in all kinds of social life for this specific audience. Within the framework of this legislation, accessibility must be ensured across different contexts inside lives of people with disabilities, with the aim of dismantling attitudinal, mobility, social, and communication barriers. This research is about Non-Governmental Organizations (NGOs) for people with disabilities (PwD), which are part of the third sector and provides support to individuals facing social vulnerability. In these spaces, PwD receive social assistance, education, and treatment through therapies designed to address multiple disabilities. These organizations offer preparation for the daily challenges of the workforce and foster social inclusion through technical and vocational education. However, despite the advancements in Technology, Digital Information, and Communication (TDICs) and assistive technologies, there are financial and technological challenges, as well as non-compliance with prevailing legislation regarding digital accessibility for this specific audience within NGOs and their daily lives.The primary objective of this thesis is to analyze digital accessibility for people with disabilities in Brazilian NGOs. This analysis is conducted from the rhizomatic perspective from Deleuze and Guattari (2011) and incorporates cartographic methods according by Petermann (2015), Rosário (2016), and Kastrup (2007). Data collection techniques encompass bibliographic and documentary research, along with an information survey. This approach facilitates the creation of four maps (plateaus) that encapsulate the various aspects. Each plateau, resulting in a continuous exploration of tensions, deterritorializations, and thematic connections relating to our research subject. The results underscore the significance of digital accessibility for these organizations in the context of digital, social, economic, and professional inclusion of PwD served by NGOs. Despite this importance, various barriers persist in relation to accessible digital communication. It is essential for public policies and science and technology initiatives to enhance the effectiveness of digital accessibility in the daily lives of people with disabilities in Brazil, with the ultimate goal of achieving their technological and social inclusion.